2008
DOI: 10.1016/j.scitotenv.2008.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of heavy metals and their effects on the midgut cells of a phytopaghous insect inhabiting volcanic environments

Abstract: Organisms living in volcanic environments are chronically exposed to metals, either as particles or associated with gases, from volcanic emissions, being therefore potential sentinels of the effects derived from such exposure. Concentrations of Ca, Cd, Cu, Mg, Mn, Pb, Rb, and Zn were measured in soil, grass (Lolium perenne), and larvae of Pseudaletia uninpuncta captured in sites exposed and non-exposed to volcanic activity. The midgut epithelial cell morphometry and apoptosis of P. unipuncta larvae were also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…concentrations. It has been recorded previously that the high mineralisation and trace element bioavailability in Furnas soils and water together, together with diffuse degassing phenomena, do influence the tissue accumulation of metals by representatives of the local fauna (Cruz et al, 1999;Cunha et al, 2008;Rodrigues et al, 2008;Viveiros et al, 2009). Tissue metal concentrations (especially Zn and Cu) in earthworms at the end of the experimental exposure to Furnas soil were found to be almost two-fold higher than the soil concentrations, and even similar to what was found in earthworms living in, or inoculated into, polluted sites (Ruiz et al, 2009).…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…concentrations. It has been recorded previously that the high mineralisation and trace element bioavailability in Furnas soils and water together, together with diffuse degassing phenomena, do influence the tissue accumulation of metals by representatives of the local fauna (Cruz et al, 1999;Cunha et al, 2008;Rodrigues et al, 2008;Viveiros et al, 2009). Tissue metal concentrations (especially Zn and Cu) in earthworms at the end of the experimental exposure to Furnas soil were found to be almost two-fold higher than the soil concentrations, and even similar to what was found in earthworms living in, or inoculated into, polluted sites (Ruiz et al, 2009).…”
Section: Chemical Analysismentioning
confidence: 99%
“…The extant volcanic activity in certain terrestrial locations on São Miguel, one of the nine islands comprising the Azores archipelago, provide good ''field-laboratories'' for investigating aspects of the capacity of soil-dwelling macroinvertebrates to inhabit natural habitats continuously receiving potentially toxic chemical inputs in a milieu conducing bioavailability (Amaral et al, 2006b;Cunha et al, 2008;Rodrigues et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination from heavy metals has become a worldwide environmental concern due to their persistence and bioaccumulation and for causing serious environmental problems to the human environment [1][2][3]. In an aquatic system, heavy metals can migrate from the water to sediments and some of these pollutants can be desorbed from the sediments and…”
Section: Introductionmentioning
confidence: 99%
“…plants to insects (Vickerman and Trumble, 2003;Mulder and Breure, 2006). Indeed, phytophagous insect (Pseudaletia uninpuncta) larvae collected from volcanic environments showed higher levels of Cu, Mn, Rb and Zn, and higher levels of apoptosis in cells from digestive epithelium due to larval chronical exposures to metals as compared with those unexposed to the volcanic activity (Rodrigues et al, 2008). Several studies have also demonstrated the relationship between the tissues damages and the accumulation of excess metals in insect body (Kawakami et al, 2013).…”
Section: Introductionmentioning
confidence: 99%